PENGARUH PELATIHAN KARYAWAN, PEMBELAJARAN KARYAWAN, DAN PENGEMBANGAN KARYAWAN TERHADAP KINERJA KERJA KARYAWAN DAN BUDAYA ORGANISASI - Irwan, Khairunnisa Salsabila; Suwarto, FX. (POLITEKNIK LP3I JAKARTA, 2026)
This study was conducted to analyze the influence of training, learning, and employee development on employee performance and organizational culture. This study used 253 respondents from different industries and companies with purposive sampling techniques, using an online survey method and questionnaires. In addition, the analysis was conducted using PLS-SEM modeling. The results of this study found that employee training had a positive influence on employee performance. Employee development has a positive influence on employee job performance. Organizational culture also has a positive influence on employee job performance. Employee training has a positive influence on work culture, and employee development also has a positive influence on organizational culture. However, there are studies that show negative results, namely between employee learning and employee work performance, as well as between employee learning and organizational culture. This study shows the importance of the company's role in providing training and development to employees to support employee work performance and organizational culture.